Association between aggression and ADHD polygenic scores and school-age aggression: the mediating role of preschool externalizing behaviors and adverse experiences - Bouliane, Mélanie; Boivin, Michel; Kretschmer, Tina; Lafreniere, Bianca; Paquin, Stéphane; Tremblay, Richard; Côté, Sylvana; Gouin, Jean Philippe; Andlauer, Till F.M.; Petitclerc, Amélie; Ouellet-Morin, Isabelle (European Child & Adolescent Psychiatry, 2025)
Individual differences in physical aggression (PA) are largely heritable. However, it remains unclear how genetic propensity for aggression manifests early in life and relates to school-age PA. Preschool externalizing behavior problems (EXT) and adverse experiences are known predictors of school-age PA and also partly heritable. We investigated whether early childhood EXT and adverse experiences mediated the association between polygenic scores and school-age PA. Genotype data collected from 721 participants in the Quebec Longitudinal Study of Child Development (45% males) were used to derive polygenic scores for aggression (PGSAGG) and attention deficit/hyperactivity disorder (PGSADHD). PA was reported annually or biennially on six occasions between ages 6 and 13 by distinct teachers. Mothers reported EXT (PA, hyperactivity, opposition) and adverse experiences (peer difficulties and harsh parenting) on three occasions between ages 3½ and 5. Both PGSs proved significant predictors of school-age PA. However, no early behaviors or adverse experiences mediated the association between PGSAGG and school-age PA. Contrastingly, hyperactivity and opposition each partially mediated the association between PGSADHD and school-age PA. Notably, when both mediators were included in the same model, only hyperactivity remained significant. This study contributes to identifying early manifestations of genetic risk for PA, which may serve as early targets for intervention.
CRIS-Team Scopus Importer:2025-03-19
Keywords: Adverse experiences; Aggression; Attention deficit/hyperactivity disorder; Externalizing behavior problems; Longitudinal study; Polygenic score